Transformation of Krinok to Bungo Krinok Music: The Innovation Certainty and Digital-Virtual Contribution for Cultural Advancement - Mahdi Bahar; Johannes Johannes; Uswan Hasan; Indra Gunawan; Zulkarnain Zulkarnain; Hartati M; Fatonah Fatonah (Pascasarjana Institut Seni Indonesia Surakarta, 2021)
Innovation is a certainty for the development of folk music. The use of digital technology is part of the creation of folk music in the sense of evolution itself. Krinok music is one of Jambi’s traditional music themes. This music genre is a cultural wealth that has great potential for artistic development and advancement. Musical systems, melodic contours, musical grammar, and interval patterns make up the distinctive character of krinok music. The normative freedom of the singing text’s spontaneous expression in presenting this musical entity and its changes is the entity that colors this uniqueness. The contribution of digital technology in processing krinok music has the potential for reproduction and publication as an integral part of the creative process itself. The placement of krinok music as cultural property is an effort to process it creatively. The result was the birth of new music as a transformation of Jambi folk music called “bungo krinok” music. This creative activity is an effort to progress the Indonesian nation’s culture.